2022
DOI: 10.3389/fonc.2022.854437
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Teratoid Rhabdoid Tumor: A Possible Oriented Female Pathology?

Abstract: Atypical teratoid rhabdoid tumor is a rare lesion that occurs mainly in children can be supratentorial or infratentorial and it accounts for 1-2% of pediatric brain tumors and over 10% of central nervous system (CNS) tumors in infants, with a male preponderance up to 3 years of age, more than 50% of these occur in the cerebellum. In this report we describe four new cases of sellar AT/RTs underwent endoscopic endonasal approach and different adjuvant therapies. Our aim is to report the clinical, radiological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“… 7 In infants, ATRTs typically arise in the posterior fossa; in adults, they more commonly occur in the supratentorial region. 2 , 3 , 8 , 9 Among adults, approximately 60 cases of ATRT have been reported in the sellar region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 In infants, ATRTs typically arise in the posterior fossa; in adults, they more commonly occur in the supratentorial region. 2 , 3 , 8 , 9 Among adults, approximately 60 cases of ATRT have been reported in the sellar region.…”
Section: Discussionmentioning
confidence: 99%
“…7 In infants, ATRTs typically arise in the posterior fossa; in adults, they more commonly occur in the supratentorial region. 2,3,8,9 Among adults, approximately 60 cases of ATRT have been reported in the sellar region. Molecular genetic analysis of the ATRT case presented in this study revealed compound heterozygous SMARCB1 point mutations, specifically the SMARCB1 L135fs c.403delC and SMARCB1 Q260* c.778C > T variants.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic–pituitary metastatic lesions represent a very challenging diagnosis: clinical signs are not different from the other lesions affecting this area, and there are no pathognomonic signs at MRI or CT scan ( 6 , 26 ). Moreover, the lack of a certain presence of tumor history jeopardizes the likelihood of a lesion of the hypothalamic–pituitary region being a metastasis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extracted DNA was converted using bisulfite (EZ gold Kit, Zymo Research, Irvine, CA, USA), following the manufacturer's instructions. The bisulfite-treated DNA was analyzed using the Illumina EPIC ARRAY 850 Bead-Chip (Infinium human methylation EPIC, Illumina, San Diego, CA, USA), as described in [9]. The array covered 850.000 CpG distributed across the genome.…”
Section: Classification Based On Dna Methylation Profilingmentioning
confidence: 99%